“Sistema de control interno en área de rentas, y mejora de recaudación fiscal de la Municipalidad Provincial de Sánchez Carrión, 2016” - Ramos Laiza, Catalina Alcira (2019)
ABSTRACT The present investigation has as objective, to determine that the implementation of a system of internal control in the area of rents, allows to improve the fiscal collection of the provincial Municipality of Sánchez Carrion, the year 2016, for which we have used the type of descriptive, not experimental, cross – sectional research. The population was the provincial Municipality of Sánchez Carrion and the sample, was composed of nine people: The alcalde. Municipal manager, head of income, head of human resources, auditor, assistant chief of income, tax manager of rents, treasurer and manager of box. The technique used was interview and as an instrument, we applied the interview guide. Among other found results and formulated conclusions we have that, the internal control in the provincial Municipality of Sánchez Carrion and in the area of rents is bad, there is no updated cadastral registry of taxpayer, there is absence of training to the income personnel, the executives of municipality, the do not comply with the application of the internal control rules issued by the General Comptroller of the Republic and the delinquency in the collection of taxes and municipal taxes is high.